IMPLEMENTASI METODE SAVI (SOMATIS, AUDITORI, VISUAL, INTELEKTUAL) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Rombe, Eni (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
The use of method in the learning process is something which can support the success of that learning process. The use of teaching method should be appropriate with the material,  the learning purpose which is wanted to be achieved. It should also observe the learning style and the various intelligence of each students. The use of SAVI (Somatic, Auditory, Visual, Intellectual) Method is very helpful because in the learning process, teacher will invoked and activate all of the human senses of the students. Therefore, the students will be motivated or enthusiastic during the learning process. The students’ learning motivation determines the achievement of the learning process purpose maximally. The result of this research  are: the first and the second hypothesis are proved because the Lower Bound and the Upper Bound values are in the medium category. The third hypothesis is rejected because the coefficient correlation value is 0.380 which is in the low category. The coefficient determination value which shows the contribution of X variable to Y variable is only 0.145 or 14.5% while the rest value which is 0.855 or 85.5%, comes from other research.  The similarity of the simple linier line is Y = 70.654 + 0.256X